2019
DOI: 10.1136/bmjopen-2018-022820
|View full text |Cite
|
Sign up to set email alerts
|

What are the social predictors of accident and emergency attendance in disadvantaged neighbourhoods? Results from a cross-sectional household health survey in the north west of England

Abstract: ObjectivesThe aim of this study was to identify the most important determinants of accident and emergency (A&E) attendance in disadvantaged areas.Design, setting and participantsA total of 3510 residents from 20 disadvantaged neighbourhoods in the North West Coast area in England completed a comprehensive public health survey.Main outcome measuresParticipants were asked to complete general background information, as well as information about their physical health, mental health, lifestyle, social issues, housi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
2
34
1
Order By: Relevance
“…Most participants (89%, n = 3844) indicated that they were of white European ethnic background. Compared with census data for the north west of England, the sample was biased towards female (study sample: 57% versus census: 51%) and black and minority ethnic (study sample: 11% versus census: 8%) participants 37…”
Section: Discussionmentioning
confidence: 94%
“…Most participants (89%, n = 3844) indicated that they were of white European ethnic background. Compared with census data for the north west of England, the sample was biased towards female (study sample: 57% versus census: 51%) and black and minority ethnic (study sample: 11% versus census: 8%) participants 37…”
Section: Discussionmentioning
confidence: 94%
“…The NWC is one of the most disadvantaged areas in the country, with consistently higher rates of premature mortality, illness, hospital admissions, mood and anxiety disorder [20]. Specifically, the NWC Household Health Survey (HHS) has shown how socio-economic issues are linked to variations in healthcare utilisation and suggests the need to address both socio-economic issues and structural issues, such as public transport and access to primary care [21,22]. This study explored the experiences of secondary mental health care service users use of the Life Rooms.…”
Section: Introductionmentioning
confidence: 99%
“…The NWC Household Health Survey (HHS) has collected information on a number of demographic and neighbourhood level characteristics, health, mental health, lifestyle, social capital, and health care utilisation. Previous analysis of the HHS has shown that being unemployed and living in poor quality housing, as well as living further from a GP practice, were linked to increased rates of Accident and Emergency (A&E) attendance [9]. This may suggest sub-optimal health management by not approaching primary care services first, but instead attending A&E. Furthermore, comorbid mental health problems have also been linked to increased healthcare utilisation in general [10].…”
Section: Introductionmentioning
confidence: 99%